The challenges of asymmetric mating - the influence of male and female size on the reproductive output of Acanthochondria cornuta (Chondracanthidae). - Frade, D.G., S. Nogueira, M.J. Santos & F.I. Cavaleiro (Parasitology, 2016)
The reproductive strategy of Acanthochondria cornuta, a parasitic copepod with dwarf, hyperparasitic males, is described in detail. The potential impact of male parasitism on the reproductive output was evaluated by determining the size of each sex and the female’s fecundity, egg size and total reproductive effort for each pair/trio throughout the four seasons of the year. Marked seasonal differences were observed in female size and reproductive output, suggesting two distinct genera- tions, but no differences were observed for male size. No statistically significant correlations were observed between male size and any measure of reproductive effort, but females with larger males had lower fecundity. A trade-off between egg number and egg size was recorded. Overall, the reproductive effort in A. cornuta seems to be determined mostly by female size, and larger females do not hold smaller males. Key words: sexual size dimorphism, reproductive strategy, parasitic copepods, Chondracanthidae, Acanthochondria cornuta.